Modyular na pagtuturo ng buhay ni Isagani sa "El Filibusterismo" sa mga estudyanteng di-tagalog sa kolehiyo volume IV - Esquejo, Cristina E. 1943- (1977)
This research study is an attempt to produce and validate a set of modular instructional materials on the sub-plot ISAGANI in the novel EL FILIBUSTERISMO by Rizal. It is based on the text translated by Patricio Mariano. Ideas and sentiments involved in the lessons are in consonance with Rizal's nationalistic philosophies worthy of appreciation by our youth today.